Descriptive Analysis of Carbon Emission Trends, Potential Carbon Tax Burden, and Emission Disclosure Levels Based on GRI 305 Indicators: A Study of Energy Sector Companies Listed on the Indonesia Stock Exchange (2022–2024) - Nadiya Salsabila; Evita Puspitasari; Saskia Salmana Dahyar (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze trends in carbon emission volume and intensity, estimate the potential carbon compliance burden under three policy scenarios, and evaluate the level of emission disclosure based on GRI 305 among energy-sector companies listed on the Indonesia Stock Exchange during 2022–2024. A descriptive approach was employed using secondary data from corporate sustainability reports. The sample comprised 39 companies and 117 observations selected through purposive sampling. Emission disclosure was assessed using the 2024 sustainability reports. The data were analyzed using descriptive statistics, scenario analysis, and quantitative content analysis. The scenario analysis included a full-rate scenario as the worst-case scenario, as well as cap-and-tax and cap-and-trade scenarios in which the emissions cap was derived through a top-down mechanism from the 2030 ENDC target using a Linear Reduction Factor and allocated through a grandfathering approach. The results show that carbon emissions tended to increase, particularly Scope 1 emissions, while Scope 2 emissions exhibited a more fluctuating pattern. This increase was accompanied by higher emission intensity, indicating that emissions relative to corporate revenue did not decline during the study period. Estimated carbon compliance costs differed substantially across scenarios. The full-rate scenario generated the highest aggregate burden of IDR 2.20 trillion, followed by the cap-and-trade (emission offset) scenario at IDR 434.90 billion, while the cap-and-tax scenario produced the lowest burden of IDR 273.81 billion. The average Carbon Emission Disclosure Index was 79.83%, with 56.4% of companies classified as well applied to fully applied.